2016
DOI: 10.1016/j.promfg.2016.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Material Removal Rate in Die-sinking Electrical Discharge Machining

Abstract: This paper proposes a semi-empirical model to predict material removal rate in die-sinking electrical discharging machining (EDM). Four different workpiece materials --high strength steel, high strength low alloy steel, brass, and aluminum --are utilized in the study. Full factorial experiments using peak current, on-time at two levels are selected for each workpiece material while keeping other parameters the same. The removed volumes are calculated by measuring sectional area of an EDM'ed hole and its dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Lee et al, [10] presented a detailed overview of challenges in real-time measurement of electrode wear, dependency on shape of holes and tool materials while drilling (by EDM) high strength steel, cemented carbide and titanium alloys. A semi empirical model was proposed by Izwan et al, [11] to predict the MRR of Al 6061-T6, Domex 550 MC steel, HSLA steel and brass alloy using a rotary copper electrode. The MRR was dependent on cumulative electrical charge obtained from individual sparking cycle and the highest MRR was obtained at higher Ip and a longer Ton duration.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al, [10] presented a detailed overview of challenges in real-time measurement of electrode wear, dependency on shape of holes and tool materials while drilling (by EDM) high strength steel, cemented carbide and titanium alloys. A semi empirical model was proposed by Izwan et al, [11] to predict the MRR of Al 6061-T6, Domex 550 MC steel, HSLA steel and brass alloy using a rotary copper electrode. The MRR was dependent on cumulative electrical charge obtained from individual sparking cycle and the highest MRR was obtained at higher Ip and a longer Ton duration.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions to be followed for these parameters are: the higher the better for MDR, the lower the better for EWR and the lower the better for SCD [ 38 ]. From the literature, it was observed that lower values of EWR and SCD can be obtained by lower current, pulse-on time, pulse-off time and temperature [ 39 ]. According to the design of experiments, it is not possible to select the desired parameter values so there is a requirement of optimization techniques for this problem.…”
Section: Resultsmentioning
confidence: 99%
“…Two main EDM techniques may be distinguished, namely die-sinking EDM and wire cutting EDM. The die-sinking EDM uses an electrode to plunge into a workpiece and create a negative shape of the electrode, while the wire EDM utilizes a uniform wire that moves continuously and gradually cuts through a workpiece (Izwan et al, 2016). A schematic of the die-sinking EDM is shown in Figure 1.6.…”
Section: Electrical Discharge Machining Methodsmentioning
confidence: 99%